The Study of Lisung-Halu as the Personification of Women in Mythical World In World View of Agrarian Sundanese - Tiara Isfiaty; Imam Santosa (Mudra Jurnal Seni Budaya, 2020)
Lisung paired with halu is one of the traditional Sundanese farming tools that has a practical function as a pestle/grain pounder into rice. From the perspective of the world view of Sundanese, lisung-halu is a cultural product that is born from the mythical logic of Sundanese. It is the manifestation of the values, norms, characteristics, desires and beliefs of agrarian Sundanese. It is the personification of male and female in world’s top (mythical world). Sundanese are oriented towards awareness of their origins. Men are considered stronger than women. But in the context of lisung-alu, the role becomes reversed. This article is descriptive qualitative by using the theory of psycho-analysis from Carl Gustav Jung to study the physical of lisung-halu (awareness output) as the personification of women in the mythical world (unconscious output) within the framework of the world view of agrarian Sundanese. The approach which is taken in this article is the cultural approach because this article is an attempt to understand the facts that refer to something. This writing is in order to generate insight and knowledge about the values of life and beliefs of the agrarian Sundanese which is contained in lisung-halu through the personification of women in mythical world.